A polyacrylamide / graphene oxide composite hydrogel, a preparation method and application thereof
Patent Information
- Application Number
- CN202310795686.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-06-30
AI Technical Summary
[0004]然而,由于地层下情况复杂,漏层处的温度通常高至一百多度,高温会降低凝胶的强度,同时高温下会减小凝胶的成胶时间,成胶时间过短的话会导致聚合物水溶液在成胶之前进入漏失通道的深度较小进而导致封堵效果差
[0055]本发明提供的聚丙烯酰胺/氧化石墨烯复合水凝胶的制备原料包括氧化石墨烯/丙烯酰胺聚合物和交联剂,所述氧化石墨烯/丙烯酰胺聚合物的制备原料包括氧化石墨烯、丙烯酰胺单体和引发剂,所述交联剂包括聚乙烯亚胺和/或酚醛树脂;首先将氧化石墨烯和丙烯酰胺单体聚合形成氧化石墨烯/丙烯酰胺聚合物,再将得到的氧化石墨烯/丙烯酰胺聚合物与交联剂进行交联,可以使最终得到的聚丙烯酰胺/氧化石墨烯复合水凝胶的具有较高的强度和较长的成胶时间,还具有优异的耐高温性能,适合应用于油气钻探开发过程中,能够有效解决高温下裂缝性地层漏失问题。
Smart Images

Figure CN117820794B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrogel technology, specifically relating to a polyacrylamide / graphene oxide composite hydrogel, its preparation method, and its application. Background Technology
[0002] In the process of oil and gas drilling and development, drilling fluid costs account for 25% to 40% of the overall cost. Drilling fluid loss in fractured formations is a common and complex situation that can lead to drilling fluid depletion and drilling time loss. In severe cases, it can cause stuck pipe, blowout, well collapse, or even wellbore abandonment, resulting in significant economic losses. Polymer aqueous solutions with added crosslinking agents enter the leakage channels in liquid form before gelation and form high-strength plugs after gelation, which can seal fractures under high pressure. The successful application of polymer gel plugging materials provides an effective way to seal severely leaky formations such as fractured and cavernous formations.
[0003] CN110655661A discloses a method for preparing a polyacrylic acid / polyacrylamide dual-network hydrogel, belonging to the field of oil well plugging technology. The dual-network hydrogel is a high-strength PAA / PAM dual-network hydrogel prepared based on acrylic acid and acrylamide. The preparation method includes: (1) preparing a silica suspension; (2) mixing a certain amount of acrylic acid, NN-dimethylacrylamide, crosslinking agent and distilled water, adding silica suspension and initiator to obtain a first mixture, and obtaining a single-network hydrogel by water bath; (3) mixing a certain amount of acrylamide, crosslinking agent, initiator and distilled water to obtain a second mixture, immersing the above single-network hydrogel in the second mixture, and obtaining a dual-network hydrogel by water bath reaction; This invention adopts a two-step aqueous solution method, water bath heating polymerization reaction, reaction under relatively mild conditions, and the obtained dual-network hydrogel has good temperature resistance, pressure resistance and good water absorption.
[0004] However, due to the complex underground conditions, the temperature at the leakage layer is usually over 100 degrees Celsius. High temperatures reduce the strength of the gel and shorten the gelation time. If the gelation time is too short, the polymer aqueous solution will enter the leakage channel to a smaller depth before gelation, resulting in poor sealing effect.
[0005] Therefore, developing a polyacrylamide / graphene oxide composite hydrogel that maintains high strength at high temperatures and has a long gelation time is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a polyacrylamide / graphene oxide composite hydrogel, its preparation method, and its application. The polyacrylamide / graphene oxide composite hydrogel maintains high strength and a long gelation time at high temperatures (90-130℃), and also exhibits excellent high-temperature resistance. It is suitable for application in oil and gas drilling and development processes and can effectively solve the problem of leakage in fractured formations at high temperatures.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a polyacrylamide / graphene oxide composite hydrogel, wherein the raw materials for preparing the polyacrylamide / graphene oxide composite hydrogel include a graphene oxide / acrylamide polymer and a crosslinking agent.
[0009] The raw materials for preparing the graphene oxide / acrylamide polymer include graphene oxide, acrylamide monomer, and initiator;
[0010] The crosslinking agent includes polyethyleneimine and / or phenolic resin.
[0011] The polyacrylamide / graphene oxide composite hydrogel provided by this invention comprises graphene oxide / acrylamide polymer and a crosslinking agent. The graphene oxide / acrylamide polymer comprises graphene oxide, acrylamide monomer, and an initiator. The crosslinking agent comprises polyethyleneimine and / or phenolic resin. This invention first polymerizes graphene oxide with acrylamide monomer to form a graphene oxide / acrylamide polymer. Then, the graphene oxide / acrylamide polymer is crosslinked with a crosslinking agent to form a gel, resulting in a polyacrylamide / graphene oxide composite hydrogel. This significantly improves the strength of the obtained polyacrylamide / graphene oxide composite hydrogel, extends the gelation time, and exhibits excellent high-temperature resistance. It avoids the problem of easy agglomeration of graphene oxide and can effectively solve the problem of leakage from fractured formations at high temperatures during oil and gas drilling and development.
[0012] Preferably, the molecular weight of the crosslinking agent is 1,500 to 150,000, such as 2,000, 4,000, 5,000, 10,000, 50,000, 100,000, 120,000, or 140,000.
[0013] Preferably, the crosslinking agent comprises polyethyleneimine.
[0014] As a preferred technical solution of the present invention, the advantage of using polyethyleneimine as a crosslinking agent is that polyethyleneimine can form covalent crosslinks with acrylamide polymers, and the crosslinking speed is low, it has good thermal stability, and compared with other metal crosslinking agents and organic crosslinking agents, polyethyleneimine crosslinking agent is low in toxicity.
[0015] Preferably, the initiator includes a peroxide initiator or an azo initiator, and more preferably an azo initiator.
[0016] Preferably, the azo initiator includes azobisisobutyronitrile (AIBN).
[0017] Preferably, the graphene oxide comprises any one or a combination of at least two of unmodified graphene oxide, carboxylated graphene oxide, or acrylamide-grafted graphene oxide, and more preferably unmodified graphene oxide.
[0018] Preferably, the raw materials for preparing the graphene oxide / acrylamide polymer also include inhibitors.
[0019] Preferably, the inhibitor comprises sodium formate.
[0020] In this invention, the addition of inhibitors can suppress the burst polymerization phenomenon that occurs in the later stage of the polymerization reaction, solve the polymer dissolution problem, and control the rate of free radical polymerization.
[0021] Preferably, the raw materials for preparing the graphene oxide / acrylamide polymer also include a pH adjuster to help adjust the pH value of the polymerization reaction solution.
[0022] Preferably, the pH adjuster comprises ammonia and / or sulfuric acid solution.
[0023] Preferably, the raw materials for preparing the graphene oxide / acrylamide polymer also include urea and / or water.
[0024] Preferably, the raw materials for preparing the graphene oxide / acrylamide polymer also include ammonium persulfate and potassium metabisulfite.
[0025] In a second aspect, the present invention provides a method for preparing the polyacrylamide / graphene oxide composite hydrogel as described in the first aspect, the preparation method comprising the following steps:
[0026] (1) Graphene oxide, acrylamide monomer, optionally an inhibitor, optionally a pH adjuster and optionally urea are mixed in water, and an initiator, optionally ammonium persulfate and optionally potassium metabisulfite are added to carry out a polymerization reaction to obtain graphene oxide / acrylamide polymer.
[0027] (2) The graphene oxide / acrylamide polymer obtained in step (1) and the crosslinking agent are gelled in water to obtain the polyacrylamide / graphene oxide composite hydrogel.
[0028] Preferably, the pH value of the system during the mixing process in step (1) is 9.5 to 10.5, such as 9.6, 9.7, 9.8, 9.9, 10, 10.1, 10.2, 10.3 or 10.4.
[0029] Preferably, the polymerization reaction in step (1) is carried out under ice bath conditions, and more preferably under ice bath conditions at 4 to 6°C.
[0030] As a preferred technical solution of the present invention, since the polymerization reaction in step (1) will release a lot of heat, in order to prevent rapid polymerization during the polymerization reaction, the polymerization reaction is carried out in an ice bath and under stirring conditions.
[0031] Preferably, step (1) specifically includes: adding acrylamide monomer, optionally an inhibitor, optionally a pH adjuster and optionally urea to an aqueous solution of graphene oxide under stirring conditions, mixing, and then slowly adding an initiator, optionally ammonium persulfate and optionally potassium metabisulfite, and carrying out a polymerization reaction under ice bath and protective gas protection to obtain graphene oxide / acrylamide polymer.
[0032] As a preferred technical solution of the present invention, adding materials in the above-mentioned specific order can better control the pH value of the polymerization reaction solution and ensure the uniformity of the mixing of each material.
[0033] Preferably, the polymerization reaction time in step (1) is 3 to 5 hours, for example, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4 hours, 4.2 hours, 4.4 hours, 4.6 hours or 4.8 hours.
[0034] Preferably, the polymerization reaction in step (1) is carried out under the protection of a protective gas.
[0035] Preferably, the protective gas includes nitrogen.
[0036] Preferably, the viscosity-average molecular weight of the graphene oxide / acrylamide polymer in step (1) is 2,000,000 to 7,000,000, such as 2,500,000, 3,000,000, 3,500,000, 4,000,000, 4,500,000, 5,000,000, 5,500,000, 6,000,000, or 6,500,000.
[0037] In the preparation method provided by the present invention, the molecular weight of graphene oxide / acrylamide polymer can be controlled by changing the mass percentage of acrylamide monomer and initiator in the polymerization reaction solution during the polymerization reaction.
[0038] Preferably, the mass percentage of graphene oxide in the polymerization reaction solution of the polymerization reaction in step (1) is 0.01-1%, for example, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6% or 0.8%.
[0039] Preferably, the mass percentage of acrylamide monomer in the polymerization reaction solution of step (1) is 13% to 33%, such as 15%, 17%, 19%, 21%, 23%, 25%, 27%, 29%, or 31%.
[0040] Preferably, the mass percentage of the inhibitor in the polymerization reaction solution of the polymerization reaction in step (1) is 0.1% to 0.2%, for example, 0.12%, 0.14%, 0.16% or 0.18%.
[0041] Preferably, the mass percentage of pH adjuster in the polymerization reaction solution of the polymerization reaction in step (1) is 0.02 to 0.08%, for example, 0.03%, 0.04%, 0.05%, 0.06% or 0.07%.
[0042] Preferably, the mass percentage of urea in the polymerization reaction solution of the polymerization reaction in step (1) is 0.02 to 0.08%, for example, 0.03%, 0.04%, 0.05%, 0.06% or 0.07%.
[0043] Preferably, the mass percentage of the initiator in the polymerization reaction solution of the polymerization reaction in step (1) is 0.05% to 0.35%, for example, 0.07%, 0.09%, 0.11%, 0.13%, 0.15%, 0.17%, 0.19%, 0.21%, 0.23%, 0.25%, 0.27%, 0.29%, 0.31%, or 0.33%, etc.
[0044] Preferably, the mass percentage of ammonium persulfate in the polymerization reaction solution of the polymerization reaction in step (1) is 0.05-0.1%, for example, 0.055%, 0.06%, 0.065%, 0.07%, 0.075%, 0.08%, 0.085%, 0.09%, or 0.095%.
[0045] Preferably, the mass percentage of potassium metabisulfite in the polymerization reaction solution of the polymerization reaction in step (1) is 0.05-0.1%, for example, 0.055%, 0.06%, 0.065%, 0.07%, 0.075%, 0.08%, 0.085%, 0.09% or 0.095%.
[0046] Preferably, the mass ratio of the graphene oxide / acrylamide polymer and the crosslinking agent in step (2) is (0.5-5):(0.005-0.3), for example, 1:0.2, 2:0.2, 3:0.2, 4:0.2, 1:0.3, 2:0.3, 3:0.3 or 4:0.3, etc.
[0047] Preferably, the gelation temperature in step (2) is 20 to 50°C, such as 23°C, 26°C, 29°C, 32°C, 35°C, 38°C, 41°C, 44°C, or 47°C.
[0048] Preferably, the gelation time in step (2) is 30 to 50 hours, such as 32 hours, 34 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, 45 hours, or 48 hours.
[0049] As a preferred embodiment of the present invention, the preparation method includes the following steps:
[0050] (1) Add acrylamide monomer, optionally an inhibitor, optionally a pH adjuster and optionally urea to an aqueous solution of graphene oxide and mix them. Add an initiator, optionally ammonium persulfate and optionally potassium metabisulfite under the protection of an ice bath and a protective gas and carry out a polymerization reaction for 3-5 hours to obtain graphene oxide / acrylamide polymer.
[0051] (2) The graphene oxide / acrylamide polymer obtained in step (1) and the crosslinking agent are gelled in water to obtain the polyacrylamide / graphene oxide composite hydrogel.
[0052] Thirdly, the present invention provides an application of the polyacrylamide / graphene oxide composite hydrogel as described in the first aspect in sealing high-temperature and high-pressure lost circulation wells in oilfields.
[0053] Preferably, the application includes its application in the sealing process.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] The polyacrylamide / graphene oxide composite hydrogel provided by this invention comprises graphene oxide / acrylamide polymer and crosslinking agent. The graphene oxide / acrylamide polymer comprises graphene oxide, acrylamide monomer, and initiator. The crosslinking agent comprises polyethyleneimine and / or phenolic resin. First, graphene oxide and acrylamide monomer are polymerized to form graphene oxide / acrylamide polymer. Then, the obtained graphene oxide / acrylamide polymer is crosslinked with the crosslinking agent. This allows the final polyacrylamide / graphene oxide composite hydrogel to have high strength and a long gelation time, as well as excellent high-temperature resistance. It is suitable for application in oil and gas drilling and development processes and can effectively solve the problem of leakage in fractured formations at high temperatures. Attached Figure Description
[0056] Figure 1 Scanning electron microscope image of GO provided for Preparation Example 1;
[0057] Figure 2 An atomic force microscopy image of GO provided in Example 1;
[0058] Figure 3 XRD pattern of GO provided in Example 1;
[0059] Figure 4 XRD comparison diagrams of GO provided in Preparation Example 1 and GO-COOH provided in Preparation Example 2;
[0060] Figure 5 A comparison of the FTIR spectra of GO provided in Preparation Example 1 and GO-COOH provided in Preparation Example 2;
[0061] Figure 6 Raman spectrum of GO provided in Preparation Example 1;
[0062] Figure 7 A comparison of the FTIR spectra of ZGOPAM-PEI-1 provided in Example 1 and PAM-PEI provided in Comparative Example 1;
[0063] Figure 8 The viscosity of the PAM-PEI system provided for Comparative Example 1 and the PAM-PEI-GO system provided for Comparative Example 2 varies with time.
[0064] Figure 9 The viscosity of the PAM-PEI system provided in Comparative Example 1 and the PAM-PEI-GO-COOH system provided in Comparative Example 3 changes over time.
[0065] Figure 10 The viscosity of the PAM-PEI system provided for Comparative Example 1 and the PAM-PEI-GO-AAM system provided for Comparative Example 4 varies with time.
[0066] Figure 11 The viscosity of the PAM-PEI system provided in Comparative Example 1 and the ZGOPAM-PEI-1 system provided in Example 1 varies with time.
[0067] Figure 12 The temperature-crosslinking time curve of ZGOPAM-PEI-1 provided in Example 1;
[0068] Figure 13 The plugging pressure diagram of ZGOPAM-PEI-1 provided in Example 1;
[0069] Figure 14 The plugging pressure diagram of ZGOPAM-PEI-2 provided in Example 2;
[0070] Figure 15 The plugging pressure diagram of ZGOPAM-PEI-3 provided in Example 3;
[0071] Figure 16 The plugging pressure diagram of ZGOPAM-PEI-4 provided in Example 4;
[0072] Figure 17 The plugging pressure diagram of ZGOPAM-PEI-5 provided in Example 5;
[0073] Figure 18 The plugging pressure diagram of ZGOPAM-PEI-6 provided in Example 6;
[0074] Figure 19 The diagram shows the pressure variation curves of the polyacrylamide / graphene oxide composite hydrogels provided in Examples 1-6.
[0075] Figure 20 The temperature-blocking pressure variation curve of ZGOPAM-PEI-1 provided in Example 1. Detailed Implementation
[0076] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0077] The following is some information about the raw materials involved in the specific embodiments of this invention:
[0078] Polyethyleneimine: molecular weight 70,000, purchased from Aladdin Reagent Co., Ltd.
[0079] Nonionic polyacrylamide: molecular weight 12,000,000, purchased from Xinbang Environmental Protection Technology Co., Ltd.
[0080] 2,2,6,6-Tetramethylpiperidine-1-oxy-terminated polystyrene: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0081] Azobisisobutyronitrile: Aladdin Reagent Co., Ltd.;
[0082] Acrylamide monomer: used after recrystallization and activated carbon adsorption.
[0083] Preparation Example 1
[0084] A graphene oxide (GO) preparation method includes the following steps:
[0085] (1) Pre-oxidation of graphite: 2.4g of potassium persulfate and 2.5g of phosphorus pentoxide were added to a four-necked flask. While stirring, 50g of concentrated sulfuric acid was slowly added. The mixture was heated to 80°C in a water bath. 5g of graphite powder was added at 80°C. The mixture was reacted at room temperature for 6 hours to obtain a reaction solution. The reaction solution was filtered with distilled water and washed several times. The solid obtained by filtration was placed in a vacuum drying oven at 60°C and dried for 12 hours to obtain pre-oxidized graphite.
[0086] (2) Preparation of graphene oxide: 5g of pre-oxidized graphite obtained in step (1) and 2.5g of sodium nitrate were added to a four-necked flask. Then, 10g of concentrated sulfuric acid with a mass fraction of 98.3% was added to each of the five batches. 15g of potassium permanganate was slowly added under ice-salt bath conditions (0-5℃). The reaction was kept at room temperature for 30min. Then, the temperature was heated to 35℃ in a water bath and kept at that temperature for 3.5h. After that, 230mL of distilled water was added dropwise using a constant pressure dropping funnel. The reaction was carried out at 97℃ for 30 min. 5 mL of 38% hydrochloric acid solution and 10 mL of 30% hydrogen peroxide were added to the flask to obtain the reaction solution. The reaction solution was transferred to a beaker, diluted with distilled water to 800 mL, and allowed to stand until it separated into layers. After separation, the upper clear liquid was discarded, and the solution was diluted with distilled water to 800 mL again. This process was repeated 3 times. The lower precipitate was then poured into a dialysis bag and dialyzed for 7 days (with water changed daily) to obtain the graphene oxide.
[0087] Preparation Example 2
[0088] A carboxylated graphene oxide (GO-COOH) is prepared by the following steps:
[0089] (1) Synthesis of succinic acid acyl peroxide: Take appropriate amounts of hydrogen peroxide, succinic anhydride (SA) and deionized water, and add them to a 50 mL three-necked flask in a ratio of m(H2O2):m(SA):m(H2O) = 1.0:1.3:1.9. Stir in an ice bath (around 8°C) for 3 h until a white gel appears. After standing for 3 h, filter under reduced pressure to obtain a solid product, and dry it under vacuum at 50°C for 24 h to obtain succinic acid acyl peroxide.
[0090] (2) Preparation of carboxylated graphene oxide: 0.2g of GO provided in Preparation Example 1 and 30mL of DMF were added to a 100mL three-necked flask and ultrasonically dispersed at room temperature for 2h to obtain a GO suspension; the temperature was raised to 85℃ and reacted for 24h. During this process, 0.6g of succinic acid peroxide obtained in step (1) was added every 8h. After the reaction was completed, the mixture was cooled to room temperature and filtered under reduced pressure to obtain a solid product. The product was repeatedly washed with DMF on a vacuum filtration flask with a microporous filter membrane to remove impurities. The product was then vacuum dried at 80℃ for 12h to obtain the carboxylated graphene oxide.
[0091] Preparation Example 3
[0092] A method for preparing acrylamide-grafted graphene oxide (GO-AAM) includes: placing 30 mg of GO provided in Preparation Example 1 into a 250 mL dry four-necked flask, then adding 50 mL of a DMF / water mixture with a volume ratio of 9:1, stirring and ultrasonically dispersing for 30 min, then adding 0.0124 g of NaBH4 (0.0032 mol), heating the solution in an oil bath at 80 °C for 4 h, and then adding PS-T (2,2,6,6-tetramethylpiperidin-1-oxy-terminated polystyrene). The acrylamide-grafted graphene oxide (PS) was prepared by stirring in an oil bath at 125°C under nitrogen atmosphere for 6 hours. The mixture was then cooled to room temperature and precipitated in methanol. The black flocculant was soaked in toluene for 48 hours to remove the homopolymer PS. The mixture was then vacuum filtered through a 0.2 μm polytetrafluoroethylene membrane and rinsed three times with double-distilled water (3 × 50 mL). The remaining black solid was then vacuum dried to obtain the acrylamide-grafted graphene oxide.
[0093] For details, please refer to "Mingyi Tang, Xiaoyang Xu, Tao Wu, Sai Zhang, Xianxian Li, Yi Li. Polyacrylamide grafting of modified graphene oxides by in situ freeradical polymerization [J]. Materials Research Bulletin, 2014, 60".
[0094] Example 1
[0095] A polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-1) is prepared by the following steps:
[0096] (1) After ultrasonically dispersing the aqueous solution of GO (Preparation Example 1), an aqueous solution of acrylamide was added to it under stirring. Sodium formate aqueous solution, urea aqueous solution and ammonia water were added while stirring. The pH value was measured with an electronic pH meter. Then, the pH of the system was adjusted to 10.0 using a prepared sulfuric acid solution (concentration of 0.01 mol / L). The mixture was stirred while maintaining it in an ice bath (1°C) and nitrogen gas was continuously introduced for 30 min while stirring. Then, APS, PMS and azobisisobutyronitrile were slowly added to it and stirred for 5 min to obtain the polymerization reaction solution. Finally, the reaction was carried out in an ice bath (5°C) for 4 h. After deionized water dialysis, drying, pulverization and sieving, the graphene oxide / acrylamide polymer was obtained.
[0097] In the polymerization reaction solution, the mass percentage of graphene oxide is 0.2%, the mass percentage of acrylamide is 18%, the mass percentage of sodium formate is 0.184%, the mass percentage of urea is 0.06%, the mass percentage of NH3·H2O is 0.04%, the mass percentage of APS is 0.0736%, the mass percentage of PMS is 0.0736%, and the mass percentage of azobisisobutyronitrile is 0.35%.
[0098] (2) The aqueous solution of graphene oxide / acrylamide polymer prepared in step (1) and the aqueous solution of polyethyleneimine are mixed to obtain a gel reaction solution, which is then gelled at 30°C to obtain the polyacrylamide / graphene oxide composite hydrogel; wherein, the volume ratio of the aqueous solution of graphene oxide / acrylamide polymer to the aqueous solution of polyethyleneimine is 9:1, and the mass percentage of graphene oxide / acrylamide polymer in the gel reaction solution is 2%, and the mass percentage of polyethyleneimine is 0.3%.
[0099] Example 2
[0100] A polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-2) differs from Example 1 only in that the mass percentage of acrylamide in the polymerization reaction solution in step (1) is 13%, while the other substances, conditions and steps are the same as in Example 1.
[0101] Example 3
[0102] A polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-3) differs from Example 1 only in that the mass percentage of acrylamide in the polymerization reaction solution in step (1) is 23%, while the other substances, conditions and steps are the same as in Example 1.
[0103] Example 4
[0104] A polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-4) differs from Example 1 only in that the mass percentage of acrylamide in the polymerization reaction solution in step (1) is 28%, while the other substances, conditions and steps are the same as in Example 1.
[0105] Example 5
[0106] A polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-5) differs from Example 1 only in that the mass percentage of acrylamide in the polymerization reaction solution in step (1) is 33%, while the other substances, conditions and steps are the same as in Example 1.
[0107] Example 6
[0108] A polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-6) differs from Example 1 only in that the mass percentage of azobisisobutyronitrile in the polymerization reaction solution in step (1) is 0.05%, while the other substances, conditions and steps are the same as in Example 1.
[0109] Example 7
[0110] A polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-7) differs from Example 1 only in that the mass percentage of azobisisobutyronitrile in the polymerization reaction solution in step (1) is 0.08%, while the other substances, conditions and steps are the same as in Example 1.
[0111] Example 8
[0112] A polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-8) differs from Example 1 only in that the mass percentage of azobisisobutyronitrile in the polymerization reaction solution in step (1) is 0.12%, while the other substances, conditions and steps are the same as in Example 1.
[0113] Example 9
[0114] A polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-9) differs from Example 1 only in that the mass percentage of azobisisobutyronitrile in the polymerization reaction solution in step (1) is 0.15%, while the other substances, conditions and steps are the same as in Example 1.
[0115] Example 10
[0116] A polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-10) differs from Example 1 only in that GO-COOH provided in Preparation Example 2 is used instead of GO provided in Preparation Example 1, while other substances, conditions and steps are the same as in Example 1.
[0117] Example 11
[0118] A polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-11) differs from Example 1 only in that GO-AAM provided in Preparation Example 3 is used instead of GO provided in Preparation Example 1, while other substances, conditions and steps are the same as in Example 1.
[0119] Comparative Example 1
[0120] A polyacrylamide composite hydrogel (PAM-PEI) is prepared by mixing an aqueous solution of nonionic polyacrylamide (PAM) and an aqueous solution of polyethyleneimine (PEI) to obtain a gel reaction solution, and then gelling at 30°C to obtain the polyacrylamide composite hydrogel.
[0121] The volume ratio of the nonionic polyacrylamide aqueous solution to the polyethyleneimine solution is 9:1. In the gel reaction solution, the mass percentage of polyacrylamide is 2% and the mass percentage of polyethyleneimine is 0.3%.
[0122] Comparative Example 2
[0123] A polyacrylamide / graphene oxide / polyethyleneimine hydrogel (PAM-PEI-GO) is prepared by means of: preparing an aqueous solution of GO provided in Preparation Example 1, mixing it with an aqueous solution of nonionic polyacrylamide and an aqueous solution of polyethyleneimine to obtain a gel reaction solution, and gelling it at 30°C to obtain the polyacrylamide / graphene oxide / polyethyleneimine hydrogel.
[0124] In the gel reaction solution, the mass percentage of GO is 0.2%, the mass percentage of polyacrylamide is 2%, and the mass percentage of polyethyleneimine is 0.3%, with a mass ratio of 1:8:1.
[0125] Comparative Example 3
[0126] A polyacrylamide / carboxylated graphene oxide / polyethyleneimine hydrogel (PAM-PEI-GO-COOH) is prepared by means of: preparing an aqueous solution of GO-COOH provided in Preparation Example 2, mixing it with an aqueous solution of nonionic polyacrylamide and an aqueous solution of polyethyleneimine to obtain a gel reaction solution, and gelling it at 30°C to obtain the polyacrylamide / carboxylated graphene oxide / polyethyleneimine hydrogel.
[0127] In the gel reaction solution, the mass percentage of GO-COOH is 0.2%, the mass percentage of polyacrylamide is 2%, and the mass percentage of polyethyleneimine is 0.3%, with a mass ratio of 1:8:1.
[0128] Comparative Example 4
[0129] A polyacrylamide / acrylamide-grafted graphene oxide / polyethyleneimine hydrogel (PAM-PEI-GO-AAM) is prepared by mixing an aqueous solution of GO-AAM obtained in Preparation Example 3, an aqueous solution of nonionic polyacrylamide, and an aqueous solution of polyethyleneimine to obtain a gel reaction solution, and then gelling at 30°C to obtain the polyacrylamide / graphene oxide composite hydrogel.
[0130] In the gel reaction solution, the mass percentage of acrylamide-grafted graphene oxide is 0.2%, the mass percentage of polyacrylamide is 2%, and the mass percentage of polyethyleneimine is 0.3%, with a mass ratio of 1:8:1.
[0131] Performance testing:
[0132] 1. Characterization analysis of GO:
[0133] (1) Morphological characteristics:
[0134] The morphology of GO provided in Preparation Example 1 was observed using a scanning electron microscope (JEOL JEM-2100, Japan) and an atomic force microscope (SPI 3800N / SPA 400, Japan), with an accelerating voltage of 200 kV. The scanning electron microscope images of GO provided in Preparation Example 1 are shown below. Figure 1 As shown, the atomic force microscopy image of GO prepared in Example 1 was obtained. Figure 2 As shown;
[0135] from Figure 1 As can be seen, the GO provided in Preparation Example 1 has a sheet-like stacked structure, with the sheets stacked and intersecting with each other, and the thickness is extremely thin and the sheet size is low.
[0136] from Figure 2 It can be seen that the GO monolayer thickness provided in Preparation Example 1 is about 5 to 20 nm, and the lateral sheet size is less than 100 nm.
[0137] (2) X-ray diffraction test (XRD):
[0138] The phases of GO provided in Preparation Example 1 and GO-COOH obtained in Preparation Example 2 were analyzed using an X-ray powder diffractometer (D / max 2500PC, Japan). Cu K2 was used as the analytical method. αX-rays (λ = 0.15418 nm) were used to scan the GO sample from 5 to 80°. The XRD pattern of the GO sample provided in Preparation Example 1 was obtained as follows. Figure 3 As shown, the XRD comparison diagrams of GO provided in Preparation Example 1 and GO-COOH provided in Preparation Example 2 are as follows. Figure 4 As shown;
[0139] from Figure 3 It can be seen that after oxidation treatment, the diffraction peaks of graphite in the GO provided in Preparation Example 1 completely disappeared, and a new diffraction peak appeared at 2θ = 11.32° with a relatively sharp peak shape, proving that the graphite was fully oxidized. At the same time, the interplanar spacing d of GO is 0.85 nm, which is significantly higher than that of graphite (0.33 nm). This indicates that during the preparation of GO, the oxidant was inserted into the graphite sheets, causing a change in its structure, which led to the incorporation of oxygen-containing functional groups such as carboxyl, hydroxyl, and carbonyl groups, resulting in a significant increase in the interplanar spacing.
[0140] from Figure 4 It can be seen that the diffraction peak of GO-COOH provided in Preparation Example 2 is sharp at 2θ = 10.31°, but the peak intensity is slightly weaker than that of GO provided in Preparation Example 1. This is because chloroacetic acid further exfoliates the GO sheets during the carboxylation process. In addition, GO-COOH provided in Preparation Example 2 shows a broad peak at 20-30°, which also proves that the GO sheet structure has been further exfoliated. The interlayer spacing of GO-COOH is 0.92 nm, which is larger than that of GO (0.84 nm). This also indicates that the GO-COOH sheets are easier to separate under ultrasonic treatment, which will help it to be effectively dispersed in an aqueous system.
[0141] (3) Fourier transform infrared spectroscopy (FTIR):
[0142] The oxygen-containing functional groups of GO provided in Preparation Example 1 and GO-COOH provided in Preparation Example 2 were measured using a Fourier transform infrared spectrometer (Nicolet 370, USA), with a scanning range of 450–4000 cm⁻¹. -1 The FTIR spectra of GO provided in Preparation Example 1 and GO-COOH provided in Preparation Example 2 were compared as follows: Figure 5 As shown;
[0143] from Figure 5 It can be seen that after introducing oxygen-containing functional groups, the FTIR spectrum of GO provided in Preparation Example 1 mainly contains the following characteristic peaks: 3410 cm⁻¹ -1 and 1380cm -1 The absorption peaks at 1730 cm⁻¹ are the vibrational and deformational absorption peaks of the hydroxyl group; the contraction vibrational absorption peak of the carbonyl group is at 1730 cm⁻¹. -1The stretching vibration peak of the alkoxy group is at 1090 cm⁻¹. -1 The above results all indicate that the oxidant fully oxidized the graphite and successfully incorporated a series of oxygen-containing functional groups on its surface.
[0144] from Figure 5 It can also be seen that the FTIR spectra of GO provided in Preparation Example 1 and GO-COOH provided in Preparation Example 2 are both at 3400 cm⁻¹. -1 A broad absorption peak appears at 2920 cm⁻¹, which corresponds to the OH stretching vibration absorption peak in water of crystallization; -1 and 2849cm -1 The absorption peak at 1718 cm⁻¹ is attributed to the symmetric and antisymmetric vibrations of CH in the methylene group (-CH₂), while the peak at 1718 cm⁻¹ is attributed to the symmetric and antisymmetric vibrations of CH in the methylene group (-CH₂). -1 and 1620cm -1 The absorption peaks at 1380 cm⁻¹ are caused by the stretching vibrations of C=O and the stretching vibrations of the C=C double bonds on the benzene-like ring structure in GO, respectively; in addition, the absorption peak at 1380 cm⁻¹ is caused by the stretching vibrations of C=O and C=C double bonds on the benzene-like ring structure in GO, respectively; -1 and 1090cm -1 The absorption peaks at 3410 cm⁻¹ correspond to the deformation vibration of CO₂ and the stretching vibration of CO in the -COOH functional group, respectively; after carboxylation, GO-COOH shows an absorption peak at 3410 cm⁻¹. -1 The absorption peak intensity of the OH stretching vibration at 1718 cm⁻¹ increases sharply. -1 The C=O stretching vibration peak shifts significantly to lower wavenumbers, eventually coinciding with the peak at 1620 cm⁻¹. -1 The overlapping of the C=C stretching vibration peaks is due to the presence of a large number of carbonyl groups in GO-COOH after carboxylation. The strong electronegativity of carbonyl groups promotes their attraction to electrons and forms a low charge density region at C=C.
[0145] (4) Raman spectroscopy:
[0146] The composition of the GO provided in Preparation Example 1 was determined using an In Via Reflex confocal laser Raman spectrometer (In Via Reflex, UK). The wavelength of the laser was 514 nm, and the scanning range was 500–3500 cm⁻¹. -1 The Raman spectrum of GO prepared in Example 1 was obtained by testing, as shown below. Figure 6 As shown;
[0147] from Figure 6 It can be seen that the characteristic D peak and G peak of GO provided in Preparation Example 1 appear at 1348 cm⁻¹. -1 With 1605cm -1At the point where peak D is generated by the breathing vibration of sp2 atoms in the ring, peak G originates from the stretching vibration of carbon chains and sp2 atom pairs. The intensity ratio of peak D to peak G, ID / IG, is 0.84, indicating that during the oxidation of graphite, the insertion of oxidant leads to the incorporation of hydroxyl, carboxyl, and other groups at the edges of the sheets, resulting in more defects and disorder in the structure. These defects and disorder further disrupt the vibrational forbiddenness of atom pairs, causing the atom pairs to begin vibrating. This result is consistent with the analysis of XRD and FTIR, both indicating that graphite has been fully oxidized.
[0148] 2. Characterization of hydrogels:
[0149] (1) Fourier transform infrared spectroscopy (FTIR):
[0150] The polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI) provided in Example 1 and the polyacrylamide composite hydrogel (PAM-PEI) provided in Comparative Example 1 were tested using a Fourier transform infrared spectroscopy (Nicolet 370, USA). The FTIR spectra of ZGOPAM-PEI provided in Example 1 and PAM-PEI provided in Comparative Example 1 are shown in the figure below. Figure 7 As shown; where, at 3182cm -1 The tensile vibration peak designated as -NH is at 1645 cm⁻¹. -1 The nearby stripe was designated as a rocking vibration of C=O at 1115 cm. -1 The peak value at that point can be attributed to the bending vibration of CO.
[0151] from Figure 7 As can be seen, the FTIR spectrum of ZGOPAM-PEI-1 provided in Example 1 shows the stretching vibration peak of -NH in acrylamide and the peak value of CO in graphene oxide, but the peak value of GO is 3430 cm⁻¹. -1 The peak at that location disappears; while in the PAM-PEI spectrum provided in Comparative Example 1, the -NH stretching vibration corresponds to 3185 cm⁻¹. -1 and 3182cm -1 1595cm -1 The absorption peak is for the amino group, close to 1644 cm⁻¹. -1 The frequency band was assigned to the C=O rocking vibration at 2925cm. -1 The peak at 3430 cm⁻¹ can be attributed to the -CH₂- bending vibration of the alkane group. The peak corresponding to the same group has shifted, while the peak at 3430 cm⁻¹ for GO is... -1 The disappearance of the peak at 1090 cm⁻¹ indicates that ZGOPAM-PEI contains hydrogen bonds formed by GO, signifying the successful preparation of the ZGOPAM-PEI gel; simultaneously, the peak at 1090 cm⁻¹ for GO disappears. -1The peak value of CO vibration stretching was found in ZGOPAM-PEI, indicating that the polyacrylamide / graphene oxide composite hydrogel was successfully prepared in Example 1.
[0152] (2) Crosslinking kinetics curve:
[0153] The viscometers used to measure the viscosities of the following hydrogels provided: the polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-1) in Example 1, the polyacrylamide composite hydrogel (PAM-PEI) in Comparative Example 1, the polyacrylamide / graphene oxide / polyethyleneimine hydrogel (PAM-PEI-GO) in Comparative Example 2, the polyacrylamide / carboxylated graphene oxide / polyethyleneimine hydrogel (PAM-PEI-GO-COOH) in Comparative Example 3, and the polyacrylamide / acrylamide-grafted graphene oxide / polyethyleneimine hydrogel (PAM-PEI-GO-AAM) in Comparative Example 4. The specific testing procedure was as follows: the gel reaction solution was poured into a test container, and the viscosity of the system was continuously measured at 30°C with a shear rate of 0.01 s⁻¹. -1 This continues until the device reaches its maximum value.
[0154] The viscosity of the PAM-PEI system provided in Comparative Example 1 and the PAM-PEI-GO system provided in Comparative Example 2 as a function of time is shown in the graph below. Figure 8 As shown in the figure, the viscosity of the PAM-PEI system provided in Comparative Example 1 and the PAM-PEI-GO-COOH system provided in Comparative Example 3 changes with time. Figure 9 As shown in the figure, the viscosity of the PAM-PEI system provided in Comparative Example 1 and the PAM-PEI-GO-AAM system provided in Comparative Example 4 changes over time. Figure 10 As shown in the figure, the viscosity of the systems obtained from the tests of PAM-PEI provided in Comparative Example 1 and ZGOPAM-PEI-1 provided in Example 1 changes over time. Figure 11 As shown;
[0155] from Figure 8 It can be seen that after the direct addition of GO, the hydrogen bonding and other interactions between GO and polyacrylamide reduced the crosslinking points of polyethyleneimine, resulting in a decrease in viscosity and strength of the gel system after gelation, and the occurrence of flocculation.
[0156] from Figure 9 It can be seen that after the direct addition of GO-COOH, the hydrogen bonding and other interactions between GO-COOH and polyacrylamide reduced the crosslinking points of polyethyleneimine, resulting in a significant decrease in viscosity after gelation, which reduced the strength of the gel system and caused flocculation.
[0157] from Figure 10 It can be seen that after the direct addition of GO-AAM, the hydrogen bonding and other effects between acrylamide-grafted graphene oxide and polyacrylamide samples reduced the crosslinking points of polyethyleneimine, resulting in a decrease in viscosity after gelation, a reduction in the strength of the gel system, and the occurrence of flocculation.
[0158] from Figure 11 It can be seen that when graphene oxide / acrylamide polymer is gelled with polyethyleneimine, the gelation time of the system is extended to 41 hours, after which the viscosity gradually increases until it exceeds the range. This indicates that grafting GO onto the molecular chain of polyacrylamide through in-situ polymerization before gelation can greatly enhance the strength of the gel and significantly extend the gelation time of the system. This ensures that the polymer aqueous solution can fully enter the leakage channels before gelation, greatly enhancing the sealing effect. Moreover, the graphene oxide in the formed gel system can be uniformly dispersed and will not agglomerate.
[0159] (4) Molecular weight:
[0160] The viscosity-average molecular weight of the graphene oxide / acrylamide polymers provided in Examples 1-11 was measured using the one-point method in GB12005.1-89, Method for Determination of Intrinsic Viscosity of Polyacrylamide [S].
[0161] (5) Initial viscosity:
[0162] The initial viscosities of the polyacrylamide / graphene oxide composite hydrogels obtained in Examples 1–11 were tested using a digital rotational viscometer (DVNEXT model, Brookfield, Middleboro, MA, USA). The measurement temperature was 30°C, and the shear rate was maintained at 0.211 s⁻¹. -1 ;
[0163] (6) Gel formation time:
[0164] The crosslinking time (gelation time) of the polyacrylamide / graphene oxide composite hydrogels obtained in Examples 1-11 was tested using a gel time tester (DVNEXT model, Brookfield, Middleboro, MA, USA) at a temperature of 30°C.
[0165] (7) Gel strength:
[0166] The elastic modulus of the fully cross-linked gel system in the polyacrylamide / graphene oxide composite hydrogels provided in Examples 1-11 was tested using an Anton Paar MCR302 rheometer. The test temperature was controlled at 30℃ and the shear frequency was 0.01-10Hz.
[0167] The tests were conducted according to the above test methods (4) to (7), and the test results are shown in Table 1:
[0168] Table 1
[0169] Example 1 3103120.71 0.14 1505115 225.7 Example 2 2348225.79 0.93 97595 284.6 Example 3 3643969.55 0.46 173195 170.6 Example 4 3733825.00 2.32 85224 123.37 Example 5 4491325.12 4.93 66667 104.3 Example 6 4988465.59 3.9 83162 84.7 Example 7 5756532.30 7.53 50171 68.6 Example 8 5899864.19 0.5 100343 66.5 Example 9 6525000.43 16.9 8247 64.1 Example 10 6348545.20 0.11 1242 55.2 Example 11 6259225.52 0.09 1380 59.2
[0170] According to the data in Table 1:
[0171] ① As can be seen from the data in Examples 1 to 9, as the viscosity-average molecular weight of the graphene oxide / acrylamide polymer increases, the initial viscosity of the gel reaction solution gradually increases, the gelation time gradually decreases, and the elastic modulus of the gel system first increases and then decreases as the viscosity-average molecular weight increases. This is because as the viscosity-average molecular weight increases, the number of crosslinking points where the polymer and crosslinking agent can undergo crosslinking reactions increases, which increases the strength of the gel system. However, when the viscosity-average molecular weight is too large, the number of crosslinking points per unit volume increases sharply, while the number of crosslinking points in other parts decreases, thereby reducing the elastic modulus.
[0172] ② According to the data from Examples 1 and 1-11, it can be seen that replacing GO with GO-COOH and GO-AAM will result in a reduction in the gelation time of the hydrogel and a decrease in the elastic modulus.
[0173] (8) Gel formation time of the gel system at different temperatures:
[0174] The crosslinking time (gelation time) of the polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-1) provided in Example 1 at different temperatures was tested using a gel time meter (DVNEXT model, Brookfield, Middleboro, MA, USA). The temperature-crosslinking time curve of ZGOPAM-PEI-1 provided in Example 1 is shown in the figure below. Figure 12 As shown;
[0175] from Figure 12 It can be seen that as the temperature gradually increases, the crosslinking time of ZGOPAM-PEI-1 provided in Example 1 gradually decreases, and the higher the temperature, the lower the crosslinking time.
[0176] (9) Gel plugging ability:
[0177] A static crack plugging apparatus (model JHB-2) was used for testing. The mass of each gel before plugging was measured. A 3mm crack was used. The gel was added to the reservoir of the static crack plugging apparatus and connected to the nitrogen line. The valve was opened to allow the polymer to contact the front end of the crack block. At 30°C, the nitrogen cylinder was used to pressurize the system at a flow rate of 5mL / min. The curves of pressure at the front end of the crack and mass of the extruded gel at the rear end of the crack as a function of time were recorded until the entire gel system was extruded. The plugging pressure of the gel was obtained using a sensor (the plugging pressure refers to the maximum pressure on the graph). The experiment was then completed.
[0178] The sealing pressure diagrams of the polyacrylamide / graphene oxide composite hydrogels provided in Examples 1-6 were obtained by testing, as shown below. Figures 13-18 As shown; the sealing pressure variation curves of the polyacrylamide / graphene oxide composite hydrogels provided in Examples 1-6 were obtained by testing. Figure 19 As shown;
[0179] from Figures 13-18 and Figure 19 It can be seen that as the molecular weight of graphene oxide / acrylamide polymer continues to increase, the sealing and pressure-bearing capacity of the gel system increases. However, once the molecular weight increases to a certain extent, the sealing capacity gradually decreases.
[0180] (10) Blocking ability of the gel system at different temperatures:
[0181] The test steps are the same as those in (9) above, except that the measurement temperature is changed. The temperature-blocking pressure change curve of the polyacrylamide / graphene oxide composite hydrogel (ZGOPAM-PEI-1) provided in Example 1 is shown in the figure below. Figure 20 As shown;
[0182] pass Figure 20 As can be seen, the blocking ability of ZGOPAM-PEI-1 provided in Example 1 gradually decreases as the temperature rises, but the overall decrease with temperature is not significant, indicating that the gel system has strong temperature resistance.
[0183] The applicant declares that this invention illustrates a polyacrylamide / graphene oxide composite hydrogel, its preparation method, and its application through the above embodiments. However, this invention is not limited to the above process steps, meaning that this invention does not necessarily rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of the raw materials used in this invention, additions of auxiliary components, and selection of specific methods all fall within the protection and disclosure scope of this invention.
Claims
1. A polyacrylamide / graphene oxide composite hydrogel, characterized in that, The raw materials for preparing the polyacrylamide / graphene oxide composite hydrogel include graphene oxide / acrylamide polymer and crosslinking agent; The raw materials for preparing the graphene oxide / acrylamide polymer include graphene oxide, acrylamide monomer, and initiator; The crosslinking agent is polyethyleneimine.
2. The polyacrylamide / graphene oxide composite hydrogel according to claim 1, characterized in that, The molecular weight of the crosslinking agent is 1500~150000.
3. The polyacrylamide / graphene oxide composite hydrogel according to claim 1, characterized in that, The initiator includes peroxide initiators or azo initiators.
4. The polyacrylamide / graphene oxide composite hydrogel according to claim 3, characterized in that, The initiator includes azo initiators.
5. The polyacrylamide / graphene oxide composite hydrogel according to claim 3, characterized in that, The azo initiator includes azobisisobutyronitrile.
6. The polyacrylamide / graphene oxide composite hydrogel according to claim 1, characterized in that, The graphene oxide includes any one or a combination of at least two of unmodified graphene oxide, carboxylated graphene oxide, or acrylamide-grafted graphene oxide.
7. The polyacrylamide / graphene oxide composite hydrogel according to claim 6, characterized in that, The graphene oxide includes unmodified graphene oxide.
8. The polyacrylamide / graphene oxide composite hydrogel according to claim 1, characterized in that, The raw materials for preparing the graphene oxide / acrylamide polymer also include inhibitors.
9. The polyacrylamide / graphene oxide composite hydrogel according to claim 8, characterized in that, The inhibitor includes sodium formate.
10. The polyacrylamide / graphene oxide composite hydrogel according to claim 1, characterized in that, The raw materials for preparing the graphene oxide / acrylamide polymer also include a pH adjuster.
11. The polyacrylamide / graphene oxide composite hydrogel according to claim 10, characterized in that, The pH adjuster includes ammonia and / or sulfuric acid solution.
12. The polyacrylamide / graphene oxide composite hydrogel according to claim 1, characterized in that, The raw materials for preparing the graphene oxide / acrylamide polymer also include urea and / or water.
13. The polyacrylamide / graphene oxide composite hydrogel according to claim 1, characterized in that, The raw materials for preparing the graphene oxide / acrylamide polymer also include ammonium persulfate and potassium metabisulfite.
14. A method for preparing the polyacrylamide / graphene oxide composite hydrogel according to any one of claims 1 to 13, characterized in that, The preparation method includes the following steps: (1) Graphene oxide, acrylamide monomer, optionally an inhibitor, optionally a pH adjuster and optionally urea are mixed in water, and an initiator, optionally ammonium persulfate and optionally potassium metabisulfite are added to carry out a polymerization reaction to obtain graphene oxide / acrylamide polymer. (2) The graphene oxide / acrylamide polymer obtained in step (1) and the crosslinking agent are gelled in water to obtain the polyacrylamide / graphene oxide composite hydrogel.
15. The preparation method according to claim 14, characterized in that, During the mixing process described in step (1), the pH value of the system is 9.5~10.
5.
16. The preparation method according to claim 14, characterized in that, The polymerization reaction in step (1) is carried out under ice bath conditions.
17. The preparation method according to claim 14, characterized in that, The polymerization reaction in step (1) takes 3 to 5 hours.
18. The preparation method according to claim 14, characterized in that, The polymerization reaction in step (1) is carried out under the protection of a protective gas.
19. The preparation method according to claim 18, characterized in that, The protective gas includes nitrogen.
20. The preparation method according to claim 14, characterized in that, The viscosity-average molecular weight of the graphene oxide / acrylamide polymer in step (1) is 2,000,000 to 7,000,000.
21. The preparation method according to claim 14, characterized in that, The mass percentage of graphene oxide in the polymerization reaction solution of step (1) is 0.01~1%.
22. The preparation method according to claim 14, characterized in that, The mass percentage of acrylamide monomer in the polymerization reaction solution of step (1) is 13-33%.
23. The preparation method according to claim 14, characterized in that, The mass percentage of the inhibitor in the polymerization reaction solution of step (1) is 0.1~0.2%.
24. The preparation method according to claim 14, characterized in that, The mass percentage of pH adjuster in the polymerization reaction solution of step (1) is 0.02~0.08%.
25. The preparation method according to claim 14, characterized in that, The mass percentage of urea in the polymerization reaction solution of step (1) is 0.02~0.08%.
26. The preparation method according to claim 14, characterized in that, The mass percentage of the initiator in the polymerization reaction solution of step (1) is 0.05~0.35%.
27. The preparation method according to claim 14, characterized in that, The mass percentage of ammonium persulfate in the polymerization reaction solution of step (1) is 0.05~0.1%.
28. The preparation method according to claim 14, characterized in that, The mass percentage of potassium metabisulfite in the polymerization reaction solution of step (1) is 0.05~0.1%.
29. The preparation method according to claim 14, characterized in that, The mass ratio of the graphene oxide / acrylamide polymer and the crosslinking agent in step (2) is (0.5~5):(0.005~0.3).
30. The preparation method according to claim 14, characterized in that, The gelation temperature in step (2) is 20~50℃.
31. The preparation method according to claim 14, characterized in that, The gelation time in step (2) is 30~50h.
32. The preparation method according to claim 14, characterized in that, The preparation method includes the following steps: (1) Add acrylamide monomer, optionally an inhibitor, optionally a pH adjuster and optionally urea to an aqueous solution of graphene oxide and mix them. Add an initiator, optionally ammonium persulfate and optionally potassium metabisulfite under ice bath and protective gas protection conditions and carry out a polymerization reaction for 3-5 h to obtain graphene oxide / acrylamide polymer. (2) The graphene oxide / acrylamide polymer obtained in step (1) and the crosslinking agent are gelled in water to obtain the polyacrylamide / graphene oxide composite hydrogel.
33. An application of the polyacrylamide / graphene oxide composite hydrogel as described in any one of claims 1 to 13 in sealing high-temperature and high-pressure lost circulation wells in oilfields.
34. The application according to claim 33, characterized in that, The applications include those in sealing and transmutation processes.
Citation Information
Patent Citations
Physical-chemical dual-crosslinking gel particle and preparation method thereof
CN111777723A
Synthesis of graphene oxide nano hydrogel blocking agent and water-based drilling fluid
CN114605675A